Celebrate International Women's Day 1992 - Rooney, Debra (artist); Lynch, Brian; Wall, Lori; Young, Irene; Harris, Pamela; Elias, Dorothy; Kuniyuki, I.H.; Addison, Merle; Mitelman, Jacqueline (photographer) (1992)
Vancouver East Cultural Centre, 1895 Venables Street CELEBRATE International Women's Day 1992/ at the Vancouver East Cultural Centre 1895 Venables Street Reservations at 254-9578/ 4 MARCH 1992 - WEDNESDAY Vancouver Folk Music Festival presents Judy Small & Lucie Blue Tremblay coproduction with Concerted Effort Productions & Random Acts Tickets .00 Reservations at 254-9578/ 5 MARCH 1992 - THURSDAY Concerted Effort Productions, Random Acts, Sounds & Furies and Women in Music presents Razom Sestre a cappella choir Janisse Browning poet Bonnie Ferguson & Colleen Savage jazz vocalists and Judy Abrams & Rhodea Auriel Lyncaster composers & pianists Labrys Rising Dance Academy three lesbian bodies of knowledge Anita Roberts reading writer Sue McGowan, Jacqui Parker-Snedker & Carol Weaver with guests "a kind of a band" Sign language interpretation provided. Tickets: .00 Reservations at 254-9578/ 6 MARCH 1992 - FRIDAY Concerted Effort Productions, Random Acts, Sounds & Furies and Women in Music present Random Acts storytellers Reijingu Horumonzu with Corinne Lee and Kelly White multidisciplinary Taiko drummers Penny Singh a cappella gospel singer Doreen McLean contemporary acoustic guitar AYA! a cappella magic Sign language interpretation provided. Tickets: .00 Reservations at 254-9578/ PACKAGE TICKETS: Reservations for each evening can be made at VECC 254-9578. A package ticket for all three nights is available at the VFMF office (879-2931) for .00./ SPONSOR: Josephine's at 1716 Charles Street at Commercial Drive. Josephine's will be open each night after the performances. Drop in for a steamed milk, or a decaf latte, and check out the woman made art and crafts before your head home./ 7 March 1992 - International Women's Day March & Rally COMPLETING THE CIRCLE WITH FIRST NATIONS WOMEN 11:30 a.m. Gather at Queen Elizabeth Theatre Plaza (Hamilton & Georgia) 12:30 p.m. Rally at the Art Gallery - north side/ Photo: Brian Lynch/ Photo: Lori Wall/ Photo: Irene Young/ Photo: Pamela Harris/ Photo: Dorothy Elias/ Photo: I.H. Kuniyuki/ Photo: Merle Addison/ Photo: Jacqueline Mitelman/ Poster: Debra Rooney/ Press Gang Printers - a feminist worker-controlled collective